Effectiveness of a group support program in minimizing depression and hopelessness among institutionalized elderly - Damaso, Leonora L. (Animo Repository, 1992)
This study was primarily conducted to determine the effectiveness of a Group Support Program in minimizing depression and hopelessness among institutionalized elderly.The study employed the Pretest-Posttest Control Group research design. Forty institutionalized elderly from the Golden Acres were randomly chosen from 51 examinees who scored high in both depression and hopelessness. They were randomly assigned to the experimental group and the control group. Of the total respondents, 20 elderly made up the experimental group and another 20 elderly comprised the control group. A Group Support Program, devised by the researcher, was the treatment introduced to the experimental group. The control group did not get the treatment. The two groups were compared based on their pretest and posttest scores on the Beck's Depression Inventory (BDI) and Geriatric Scale of Hopelessness (GSH). The statistical tools used were t-test and ANCOVA.The results of the study pointed to the potential of the Group Support Program in lessening the feelings of depression and hopelessness among elderly respondents, and thereby supported the hypotheses of the study. The t-test performed on the pretest and posttest scores of both groups indicated significant difference in favor of the experimental group on BDI and GSH. A significant difference was found between the pretest and posttest scores of the experimental group on both the BDI, t (19) = 6.22, P .05, and the GSH, t (19) For the control group, on the other hand, no significant difference was found between their pretest and posttest scores on the BDI t (19) = .558, P .05. However, a significant difference was observed between the pretest and posttest scores on the GSH t (19) = 5.75 P .05.A significant difference was found between the adjusted posttest scores of the experimental and control groups on the BDI, F (1,37) = 22.82 P .05 and on the GSH, F (1,37) In the light of the results, recommendations were advanced on the program and on further research considerations.